Communication skills: applying the Drug-Centred Model in mental health - Armando Henrique Norman; Felipe Monte Cardoso (Interface: Comunicação, Saúde, Educação, 2025)
The disease-centred model (Disease-CM) is the hegemonic approach to mental health issues in biomedicine. Critical Psychiatry challenges this view and proposes a drug-centred model (Drug-CM). The Drug-CM is counterintuitive as physicians are trained to diagnose and treat diseases. This article presents a communication framework to facilitate the application of the Drug-CM in the consultation. Firstly, two steps of a general clinical consultation framework are presented. Secondly, in the consultation second step, three explanatory models are proposed: (a) the visible and invisible world of human beings (objectivity vs. subjectivity); (b) the absence of biological markers; and (c) the Drug-CM. Finally, two illustrative cases demonstrate the application of the Drug-CM in consultation. The improvement in communication skills via the Drug-CM can contribute to reduce medicalization in mental health.